Compensation, Teamwork, and Job Satisfaction Boost Employee Performance in Indonesia : Kompensasi, Kerja Sama Tim, dan Kepuasan Kerja Meningkatkan Kinerja Karyawan di Indonesia - Ajeng Karuniya Putri; Hasan Ubaidillah (Academia Open, 2024)
This research examines how compensation, teamwork, and job satisfaction affect employee performance at UD Rifki Muslim Jaya in Mojokerto. Limited research exists on these factors in small-scale enterprises in Indonesia, prompting this study. Using quantitative methods and random sampling, data were collected from 80 employees via questionnaires. Multiple regression analysis with SPSS showed that compensation, teamwork, and job satisfaction significantly impact employee performance both individually and collectively. The findings highlight the need for managers to enhance these factors to boost productivity and performance. Highlight: Compensation, teamwork, and job satisfaction significantly impact employee performance. Used random sampling and multiple regression analysis. Findings emphasize focusing on these factors to enhance productivity. Keywoard: Compensation, Teamwork, Job Satisfaction, Employee Performance, Quantitative Research